Phytochemical Characterization And Wound Healing Property Of Euphorbia Hirta L. - Ayoona, Daniah Fouad Abdulameer (2024)
Euphorbia hirta l, an annual plant that belongs to the euphorbiaceae family, is a common traditional remedy for several diseases. Currently, there are few investigations on this plant as a treatment for wound healing, particularly the bioactive compounds and mechanism of action. Therefore, this study focused on isolating the main active compounds associated with the wound-healing activity of e. Hirta. The aerial parts of the plant were collected from the northern part of malaysia and iraq and then were extracted with solvents of different polarities: hexane, chloroform, methanol, and water. All extracts were screened for total phenolic and flavonoid contents and antioxidant and anti-inflammatory activities. Additionally, all extracts were assessed for potential wound healing activity by measuring the migration and cell viability of human fibroblast cells, hs27. Then the methanol extracts were further fractionated to identify the active compounds. The structure elucidation of isolated compounds was confirmed using liquid chromatography-mass spectrometry (lcms/ ms), nuclear magnetic resonance (nmr), and high-performance liquid chromatography (hplc). Subsequently, molecular docking was performed on the isolated compounds to analyse their binding interactions with the glycogen synthase kinase-3β (gsk3b) and casein kinase 1 (ck1) proteins. The level of mrna expression of four cytokines (il1b, il6, tnf, and col1a1) after treating human fibroblasts with different compounds were assayed. The e. Hirta extract yielded a different type of compounds: kaempferol,